2022
DOI: 10.21203/rs.3.rs-2051625/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scleral thickness as a risk factor for central serous chorioretinopathy and pachychoroid neovasculopathy

Abstract: Background/Objectives. While the exact pathophysiology of pachychoroid disorders remains unclear, scleral changes inducing increased venous outflow resistance are hypothesized to be involved. This work aims to investigate anterior scleral thickness (AST) as a risk factor for central serous chorioretinopathy (CSC) and pachychoroid neovascularization (PNV). Subjects/Methods. Randomized prospective case-control study performed at the Ludwig Maximilians-University, Department of Ophthalmology. 46 eyes of 46 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Fraser et al ( 8) caution against unsupervised use of ChatGPT for triage without enhancements to accuracy and clinical validation. Gebrael et al (23) suggest that ChatGPT can assist healthcare providers in improving patient triage, while Knebel et al (28) found that although ChatGPT provides appropriate measures, there is a potential for harmful recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Fraser et al ( 8) caution against unsupervised use of ChatGPT for triage without enhancements to accuracy and clinical validation. Gebrael et al (23) suggest that ChatGPT can assist healthcare providers in improving patient triage, while Knebel et al (28) found that although ChatGPT provides appropriate measures, there is a potential for harmful recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging included the acquisition of a standard volume scan centered on the macula consisting of 49 equally spaced B-scans covering 20 × 20 degrees centered on the fovea (on Spectralis HRA + OCT, Heidelberg Engineering, Heidelberg, Germany) [8]. Subfoveal choroidal thickness (SFCT) was assessed by manual measurements of the distance between Bruch's membrane and the transition zone between the choroid and the sclera underneath the foveola.…”
Section: Imagingmentioning
confidence: 99%
“…Kishi and colleagues recently described a frequent overlap of areas of vortex vein dilatation and areas of reduced perfusion of the choriocapillaris in en-face optical coherence tomography (OCT) imaging in eyes with CSC [4]. They concluded that in CSC, compression of the vortex veins can lead to backflow into the venous system of the choroid and, secondarily, to anterograde filling delay of the choriocapillaris with the formation of ischemic areas [5]. This thesis is supported by the fact that in eyes with CSC, chronic overload of the venous system was observed compared with a control collective.…”
Section: Introductionmentioning
confidence: 99%